A single-blind, pilot randomised trial of a weight management intervention for adults with intellectual disabilities and obesity: study protocol. Issue 1 (December 2015) - Harris, Leanne; Melville, Craig; Jones, Nathalie; Pert, Carol; Boyle, Susan; Murray, Heather; Tobin, Janet; Gray, Fiona; Hankey, Catherine
Abstract Background The prevalence of obesity in adults with intellectual disabilities has consistently been reported to be higher than the general population. Despite the negative impact of obesity on health, there is little evidence of the effectiveness of weight management interventions for adults with intellectual disabilities and obesity. Preliminary results from a single-stranded feasibility study of a multi-component weight management intervention specifically designed for adults with intellectual disabilities and obesity (TAKE 5) and that satisfied clinical recommendations reported that it was acceptable to adults with intellectual disabilities and their carers. This study aims to determine the feasibility of a full-scale clinical trial of TAKE 5. Methods This study will follow a pilot randomised trial design. Sixty-six obese participants (body mass index (BMI) ≥30 kg/m2 ) will be randomly allocated to the TAKE 5 multi-component weight management intervention or a health education 'active' control intervention (Waist Winners Too (WWToo)). Both interventions will be delivered over a 12-month period. Participants' anthropometric measures (body weight, BMI, waist circumference, percentage body fat); indicators of activity (levels of physical activity and sedentary behaviour) and well-being will be measured at three time points: baseline, 6 and 12 months. The researcher collecting outcome measures will be blind to study group allocation. Conclusions The data from this study will generate pilot data on the acceptability of randomisation, attrition rates and the estimates of patient-centred outcomes of TAKE 5, which will help inform future research and the development of a full-scale randomised clinical trial. Trial registration ISRCTN52903778 .